Development and Validation of a Radiotherapy Administration Checklist for Patients Undergoing Radiation Therapy - ., Savita; Kumar, Ashok; ., Nimarta; Pareek, Puneet; K. Nair, Shrikant (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Radiotherapy, the use of high-energy ionizing radiation to treat diseases, is increasingly employed in cancer treatment due to technological advancements. Precision and competency are paramount in radiotherapy administration, necessitating tools to standardize care and minimize medical errors. This study aimed to develop and validate a radiotherapy administration checklist to serve as a standardized guide for the procedure. Materials and methods: A methodological research design was employed to develop the radiotherapy administration checklist. The development process involved five phases: (i) preliminary phase (literature review, focus group discussions, assessment of current practices, item pool generation, and preliminary draft preparation), (ii) validation phase (content validity assessment using the modified Delphi technique and construct validation through factor analysis), (iii) pilot testing, (iv) final trial and reliability assessment (internal consistency and inter-rater reliability), and (v) evaluation phase. Results: The final radiotherapy administration checklist comprised 29 items and demonstrated strong validity and reliability. Content validity scores (S-CVI/Avg. and S-CVI/UA) were 0.97 and 0.79, respectively. Cronbach’s alpha (0.64) and inter-rater reliability (0.76) were within acceptable ranges. Factor analysis revealed that all 29 items loaded onto eight distinct factors. Conclusion: The developed radiotherapy administration checklist is a valid and reliable tool with psychometric properties within the expected range. It can be used as a standardized tool to ensure safe, uniform, and optimal delivery of radiotherapy.